UMP beefs up its ICT security with ISO/IEC 27001 - UMP, PNC
Universiti Malaysia Pahang (UMP) was awarded ISO/IEC 27001 for Information Security Management System (ISMS) for the operational and maintenance of its Gambang Data Centre.